Coupling effect mental training with View kinetic model Learn the basic movements of the freestyle swimming - Salahaddin, Mustafa (Journal of Physical Education, 2013)
Ensure the door first search Introduction research topic and its importance in the fact that motor learning one "of science, which saw the birth of a lot of theories and research in the study of evolution in behavior according to planning, organizing proper buildings on the basis of modern scientific, it is through it was addressing the problem of search Westphalian lack of concentration and attention to the subject of training mental and watch live model movement by the learner neophyte through practical lessons for substance swim in college, although the movements swimming movements are vehicles need to think and meditate for watching the performance of a typical them before they are implemented, and on the basis that the purpose of this study to prepare exercises especially in conjunction training mental with View model kinetic live and study its impact on learning movements freestyle, and to achieve these goals has been assumed researcher for the exercise of a positive impact in learning movements freestyle, and to achieve the goals and hypothesis search has adopted researcher experimental method to work, where random selection for (30) students "of students of Physical Education College / first stage novices (do not know swimming), as it has been divided into two equal groups including one pilot and another officer and after ensuring equal and smoothing groups and application modules for searching, tested quantitatively" and qualitatively "to test (25)m freestyle, where experimental group surpassed used exercises for training mental associated watching model motor neighborhood on the control group the experimental group in the level of learning and performing movements freestyle, and based on" what has been reached from the results of the recommended researcher should introduce exercises mental training is associated with watching kinetic model neighborhood in practical lessons to teach swimming for beginners, and conduct research